(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2007)
‘Camelina sativa’ is one of the oldest oil crops in Europe. Growing areas were reduced dramatically in 20-40-ties of the last century. Low price of rape oil and unclear composition of camelina oil were primary reasons of this process. Nevertheless, last years ‘Camelina sativa' attracted a great interest of scientists and oil processors as a crop for diversification of agriculture and, in the same time, for producing of the high quantity and quality oil for biofuel, feeding, food, and pharmacy (source of a-linolenic acid, linoleic acid and vitamins, especially E). In Latvia ‘Camelina sativa' is spread as a wild form but for the agriculture it is a new crop.The potential of me of ‘Camelina sativa’ in the Latgale region as an alternative oil crop and a new plant in the crop rotation was investigated. We compared the oil content and it composition in ‘Camelina sativa ’ seeds from plants of variety ‘Ligena’ grown in different conditions (Latvia and Germany). We also are looking for a possibility to use biotechnology methods for obtaining additional camelina breeding source material. For this purpose we applied calli culture method for producing plants-regenerants.